ANALYSIS OF STUDENTS’ CREATIVE THINKING ABILITIES IN SOLVING PROBLEMS IN CHEMICAL BONDING MATERIAL FOR CLASS X SMA IN THE TOGEAN ISLAND - Pulukadang , Sri Hastuti Virgianti; Indasari, Indasari; Afadil; Mustapa, Kasmudin (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2023)
Creative Thinking is the ability possessed by someone to think continuously and consistently in producing everything that is creative and original. This study aims to analyze students' creative thinking skills in solving problems in chemical bonding material for class X high school in the Togean Islands, namely taking place in two schools, namely SMA Negeri 1 Togean and SMA Negeri 1 Una- Una. The method used in this research is descriptive. The sample in this study was students of class X mipa SMA Negeri 1 Togean totaling 21 students consisting of 10 boys and 11 girls and for SMA Negeri 1 Una-Una totaling 19 student consisting of 13 boys and 6 girls. The data collection instrument used a practice test of essay questions in the form of a description of students' creative thinking abilities on chemical bonding material as many as 8 items. The result obtained for SMA Negeri 1 Togean, the fluency indicator is 76.66% in the high category, the Flexibility indicator is 60.47% in the medium category, the Originality indicator is 45.71% in the low category and the Elaboration indicator is 31.90% in the very low and for SMA Negeri 1 Una-Una the Fluency indicator is 66.31% with the medium category, the Flexibility indicator is 76.31% with the high, the Originality indicator is 52.10% with the low category and the Elaboration indicator is 35.78% with very low category. The result of the average creative thinking ability of students for SMA Negeri 1 Togean is 53.68% is in the low category, and SMA Negeri 1 Una-Una is 57.63% and is in the low category. Based on the result of the study it can be concluded that students' creative thinking abilities are in the low category, one of the reasons is due to the laziness factor of each student in participating in ongoing learning which triggers students not to think creatively, especially in chemical bonding material